Flexural Behavior of Slab-Rib Integrated Bridge Decks with GFRP Skin and Polyurethane Foam Core - Jing Li; Jun Wang; Bishnu Prasad Yadav; Jiye Chen; Qiang Jin; Weiqing Liu (Advances in Materials Science and Engineering)
This paper presents experimental and analytical studies on flexural behavior of slab-rib integrated Sandwich composite decks. The influences of layers of glass fiber-reinforced polymer (GFRP) facesheets, foam densities, and the existence of webs and cross beams are discussed herein. The test results showed that the existence of vertical webs remarkably improved the debonding of the facesheets from the foam core, thus increasing the ultimate load by 59% compared with the specimens without webs. However, the existence of horizontal webs has insignificant effect on the failure mode and ultimate load. Increasing the number of layers of GFRP facesheets from 2 to 4 and 6 results in 100% and 214% increments in ultimate loads, respectively, while the specimen with lower density of foam had a higher ultimate load than the specimen with higher density of foam due to deformation compatibility between GFRP skins and foam core with low density. The analysis software Abaqus Explicit was used to simulate the flexural behavior of test specimens, and the numerical results agreed well with the test data. The verified finite element model was extended to analyze the influences of the number of GFRP layers on the top of decks and the height of vertical webs. Based on equivalent method and compatibility of shear deformation, the flexural and shear rigidities were estimated. Then, analytical solution for displacement of the slab-rib integrated Sandwich composite decks subjected to four-point load was derived out. Comparison of analytical and experimental results shows that the displacements can be precisely predicted by the present theoretical model.